THE KNOWLEDGE AND ATTITUDES OF TEACHERS REGARDING LEARNING DIFFICULTIES (UKLO Proceedings, 2025)
This paper aims to explore the knowledge and attitudes of teachers regarding learning difficulties, with the objective of better understanding their impact on the educational process. The focus is on analyzing teachers' awareness of various forms of learning difficulties, as well as their pedagogical approaches to creating an inclusive and supportive environment for all students. This includes the use of multisensory strategies and individualized methods to improve the inclusion of students with special educational needs. The paper also examines the challenges teachers face in addressing these difficulties and the role of collaboration between families, specialists, and educational institutions. The results show that teachers' knowledge and positive attitudes play a crucial role in the successful development of students with learning difficulties and in fostering a culture of inclusion. The research suggests that continuous teacher training and the use of inclusive pedagogical practices are essential for optimizing educational outcomes.